Evaluation of a Malaysian soy sauce koji strain Aspergillus oryzae NSK for γ-aminobutyric acid (GABA) production using different native sugars - Ahmad, Siti Hajar; Wan Mohtar, Wan Abd Al Qadr Imad; Ab Kadir, Mohd Safuan; Abd Rahim, Muhamad Hafiz; Saari, Nazamid (Springer, 2018)
In this study, a selected γ-aminobutyric acid (GABA)-rich Malaysian strain Aspergillus oryzae NSK was collected from soy sauce koji. The strain was used to explore the effect of using renewable native sugar syrup, sugarcane, nipa, and molasses as fermentable substrates for developing a novel functional GABA soy sauce. We evaluated the strain using the chosen native sugars for 7 days using shake flask fermentation at 30 °C. The results showed optimum GABA concentration was achieved using cane molasses as the fermentable substrate (354.08 mg/L), followed by sugarcane syrup (320.7 mg/L) and nipa syrup (232.07 mg/L). Cane molasses was subsequently utilized as a substrate to determine the most suitable concentration for A. oryzae NSK to enhance GABA production and was determined as 50% g/L of glucose standard cane molasses. Our findings indicate that cane molasses can be used as a GABA-rich ingredient to develop a new starter culture for A. oryzae NSK soy sauce production.